Before fiction : the ancien régime of the novel - Paige, Nicholas D. (University of Pennsylvania Press, 2011)
Before Fiction asks why so many early novelists pretended their novels were literally true when no one believed them. For Nicholas D. Paige the answer lies in a radically new view of the formal history of the novel in England and France.